2015
DOI: 10.1590/1677-5449.20140039
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between severity of signs and symptoms and quality of life in patients with chronic venous disease

Abstract: BACKGROUND: Chronic venous disease (CVD) is progressive and has a high prevalence in the economically active population. Its impact on the quality of life of affected individuals is poorly understood. OBJECTIVE: To test for correlations between the CEAP classification of CVD severity and CVD symptoms and quality of life of affected individuals. METHODS: We investigated 91 lower limbs in 59 patients with CVD (CEAP C1- C6). Patients were assessed with a Visual Analogue Pain Scale (VAPS), the Venous Clinical Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
9
1
3
Order By: Relevance
“…Consistent with these studies, we also found that patients with higher CEAP grade (C3-C4-C6) had lower mental health and QoL score compared with patients with less severe disease (C1-C2). Our study did not find any association between disease severity with physical functioning score, may be because more than half of our patients had grade 1 disease while according to Rossi [17] , in early stages, the disease mainly affects mental health. The later the stage, the more reduced the physical functioning, the more affected the work, everyday life activities, and family-social relationships.…”
Section: Average Qol Score Based On Sf-36 Scalecontrasting
confidence: 65%
“…Consistent with these studies, we also found that patients with higher CEAP grade (C3-C4-C6) had lower mental health and QoL score compared with patients with less severe disease (C1-C2). Our study did not find any association between disease severity with physical functioning score, may be because more than half of our patients had grade 1 disease while according to Rossi [17] , in early stages, the disease mainly affects mental health. The later the stage, the more reduced the physical functioning, the more affected the work, everyday life activities, and family-social relationships.…”
Section: Average Qol Score Based On Sf-36 Scalecontrasting
confidence: 65%
“…The task of the correlation analysis method is to determine correlations between the studied parameters, the nature and pronouncement of which are established by the pair correlation coefficient (Akoglu, 2018;Schober et al, 2018;Uurtio et al, 2018). Prolonged use of the method facilitated the data accumulation for studying various biomedical processes (Miot, 2017(Miot, , 2018Yadav, 2018) at their multiple levels (Rossi et al, 2015;Maranzatto et al, 2016;Kim et al, 2017), which resulted in the development of tools to facilitate visualization, analysis and interpretation of the information obtained (Mutwil et al, 2010;Batushansky et al, 2016). However, the method is not intended to work with qualitative or binary data on the state of a studied biosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Em razão da ineficácia das ações de redução de morbi-mortalidade e ausência da repercussão dos benefícios dos cuidados de saúde, na manifestação da Doença Venosa Crônica (DVC), a busca pelo conhecimento científico e clínico da doença, e de seus fatores associados, tem aumentado de forma significativa no Brasil (7) . Tais ações teriam o intuito de redução dos gastos, provenientes do tratamento dessa patologia, e diminuição da incidência das suas formas graves, por meio de uma avaliação precoce e eficiente.…”
Section: Introductionunclassified
“…Outro aspecto relevante é que, embora seja uma realidade mundial, o aumento da prevalência e da gravidade da DVC, estudos a respeito da intensidade dos sintomas e do comprometimento à qualidade de vida dos indivíduos, acometidos pela DVC, ainda são escassos (3,5,7) . Ademais, apesar de estudos apontarem que o uso de um questionário validado como VEINES QoL/Sym ® possibilita um maior conhecimento da qualidade de vida do individuo com IVC e de seu impacto funcional, psicológico e social (4,6) ,poucos estudos confrontam a gravidade dos sinais clínicos e o desenvolvimento da doença do indivíduo, atingido por essa patologia (4,6) .…”
Section: Introductionunclassified